For a new narrative (dis)order: a reading of Trans Iberic love, by Raquel Freire - Furlan, Vivian Leme [UNESP] (Univ Estadual Paulista-unesp, 2019)
Facing the need of an increasingly struggle for (re)affirmation of gender freedom in a globalized context both physically and politically, Trans Iberic love, by Raquel Freire establishes the place of literature as a force of deconstruction of binomial and retrograde discourses in a heteronormative society. In this sense, the author's ideological and creative position institutes dialogic contacts with the criticism of Joao Barrento (2016) when he defends the existence of a new narrative disorder on the female writings in the contemporaneity. From the analysis of the various narrative strategies, it is possible to point out the multiple deconstruction that this work presents, from the narrator who shatters into non-binary voices and activist and transsexual characters, to the deconstruction of textual form and genre, since the category of romance becomes insufficient in a work that can also be read as an essay on queer theory or as a manifesto. Thus, with this brief reading, we will try to demonstrate that this narrative (dis)order in literature, as well as in gender, gvnocritical and queer theories studies, function as tools to ventilate what escapes the social norm and resists to the categorization and homogenization in a society of alienating cultures and roles.
Keywords: Gender deconstruction; Queer; Raquel Freire